Diagnostic accuracy of brief cognitive screening tools to diagnose vascular cognitive impairment in Peru - Custodio, Nilton (2021)
ABSTRACT Introduction To evaluate the diagnostic accuracy of three brief cognitive screening (BCS) tools, Peruvian version of Addenbrooke's Cognitive Examination (ACE-Pe), of INECO Frontal Screening (IFS-Pe) and of the Mini-Mental State Examination (MMSE-Pe), for the diagnosis of vascular cognitive impairment (VCI) and its non-dementia stages (VCI-ND) and vascular dementia (VD) in patients with cerebral stroke in Lima—Peru. Materials and methods A cohort analysis to evaluate the diagnostic accuracy of three BCS for VCI. Results Two hundred and four patients were evaluated: 61% Non-VCI, 30% VCI-ND and 9% VD. To discriminate patients with VCI from controls, the area under the curve (AUC) of ACE-Pe, IFS-Pe and MMs-Pe were 0.99 (95% confidence interval [CI] 0.98–0.99), 0.99 (95%CI 0.98–0.99) and 0.87 (95%CI 0.82–0.92), respectively. Of the three BCS, the IFS-Pe presented a larger AUC to discriminate VCI-ND from VD (AUC = 0.98 [95%CI 0.95–1]) compared to ACE-Pe (AUC = 0.84 [95%CI 0.74–0.95]) and MMSE-Pe (0.92 [95%CI 0.86–0.99]). The IFS-Pe presented a higher sensitivity (S), specificity (Sp), and positive (+LR) and negative likelihood ratios (−LR) (S = 96.72%, Sp = 89.47%, +LR = 9.1 and −LR = 0.03) than ACE-Pe (S = 96.72%, Sp = 63.16%, +LR = 2.62 and −LR = 0.05) and MMSE-Pe (S = 90.16%, Sp = 78.95%, +LR = 4.28 and −LR = 0.12). In the multiple regression analysis, the IFS-Pe was not affected by age, sex or years of schooling. Conclusion The IFS-Pe has the best diagnostic accuracy for detecting VCI and discriminating between pre-dementia (VCI-ND) and dementia (VD) stages.